Alternative oxidase plays an important role in Paracoccidioides brasiliensis cellular homeostasis and morphological transition (2015)
ABSTRACT: Paracoccidioides brasiliensis is the etiologic agent of one of the most common systemic mycoses in Latin America. As a dimorphic fungus, it must adapt to different environments during its life cycle, either in nature or within the host, enduring external stresses such as temperature or host-induced oxidative stress. In this study we addressed the role of alternative oxidase (PbAOX) in cellular homeostasis during batch culture growth and the morphological transition of P. brasiliensis. Using a PbAOX-antisense-RNA (PbAOXaRNA) strain with a 70% reduction in gene expression, we show that PbAOX is crucial for maintaining cell viability and vitality during batch culture growth of yeast cells, in what appears to be a pH-dependent manner. We also show that silencing of PbAOX drastically reduced expression levels of other detoxifying enzymes (PbY20 and PbMSOD). In addition, our data indicate that PbAOX plays a role during the morphological transition, namely, during the yeast-to-mycelia germination and mycelia/conidia-to-yeast transition, essential events during the establishment of infection by dimorphic fungal pathogens. Altogether, our findings support the hypothesis that PbAOX is important for the maintenance of cellular homeostasis, possibly by assisting redox balancing during cell growth and the morphological switch of P. brasiliensis.